Diagnostic difficulties in a patient with generalized pustular psoriasis - Katarzyna Juczyńska (Termedia Publishing House, 2014)
Introduction . Generalized pustular psoriasis is an uncommon, severe form of psoriasis. It may have a chronic, recurrent clinical course after rapid onset. Objective . To present diagnostic problems in a patient with a medical history of rheumatoid arthritis and sudden onset of generalized pustular eruption. Case report . A 66-year-old patient with rheumatoid arthritis, treated with immunosuppressants, was admitted to our department with acute, generalized pustular eruption. Histopathological findings in skin biopsy were equivocal; however, clinical diagnosis of pustular psoriasis was established. The diagnosis was sustained in longer perspective as slow regression of pustular eruptions and chronic, recurrent nature of skin lesions were observed. Conclusions . The presented case report along with data from the literature indicate that clinical and histopathological diagnosis of pustular psoriasis can be difficult. It is suggested that immunosuppressive therapy can affect both histopathological findings and therapy outcome.